Constraints and Perspectives for Sustainable Wheat Production in Tajikistan - Husenov, Bahromiddin; Otambekova, Munira; Muminjanov, Hafiz; Morgounov, Alexey; Asaad, Siham; Garkava-Gustavsson, Larisa; Johansson, Eva (Frontiers in Sustainable Food Systems, 2020)
Wheat has a key role for food security in Tajikistan, contributing 60% of daily calorie intake for the Tajik population. An understanding of the major constraints and opportunities of wheat production and sustainability is therefore required. A survey of 210 wheat fields of different sizes, from different agricultural zones and altitudes, was conducted during three consecutive years. A questionnaire on wheat production and sustainability was applied, seeking information about farms and crop management practices, and accompanied by surveillance of field status of biotic and abiotic stresses. Also, a screening was carried out on major Tajik wheat varieties and advanced breeding lines, to assess their resistance to important diseases. The results showed that the agronomic knowledge of Tajik farmers was generally poor and that wheat yield was low, affecting social, economic, and environmental sustainability. The farms surveyed were generally small, growing winter wheat for human consumption year after year. Seeds were hand-broadcast at the optimal sowing time, without chemical treatments; farmers used nitrogen fertilizer and irrigation but no weed treatment, the latter resulted in high levels of weeds. The low knowledge status of farmers influenced crop performance and were correlated with lack of crop rotation. While some similarities were shared by most wheat fields surveyed, there was also some variation in wheat crop performance among farms in relation to their size, year of study, agricultural zone, and altitude. Wheat production on small farms still relied heavily on manual labor, while larger farms used more machinery. However, larger farms were not more successful wheat producers than small farms. Most of the Tajik wheat varieties and lines screened were susceptible to at least one of the diseases screened for, i.e. stripe rust, leaf rust, and common bunt. Our findings demonstrate a need for concerted action to overcome wheat yield constraints and achieve sustainability in crop production in Tajikistan. Education of farmers appears key to improving social, economic, and environmental sustainability. Use of certified seed of suitable wheat varieties and appropriate crop management practices, including weed control while also taking biodiversity into consideration, are other important measures for increasing wheat yield and improving sustainability.